Yann Gerstberger - Baby comet face - Baudin, Arno (Zolo Press, 2018)
This monograph provides an exhaustive look at the practice of Yann Gerstberger, a French artist exiled in Mexico, whose work is deeply rooted in Mexican popular culture and pre-Columbian mythologies. The publication gathers series of works (sketches, photocopies, neon paper drawings and collages, tapestries), two essays, and poems by Gabriela Jauregui. The edition features an annex booklet devoted to exhibition views.
Produced in a limited run of 800 copies
Keywords: Gerstberger, Yann -- 1983-